2022
DOI: 10.1371/journal.pone.0278625
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors for visual prognosis according to the types of infectious endophthalmitis

Abstract: Background Endophthalmitis is a fatal ophthalmological emergency that needs prompt diagnosis and treatment. This study aimed to evaluate the clinical characteristics and investigate risk factors for the visual prognosis of the different types of endophthalmitis. Methods This retrospective study included 239 eyes diagnosed with endophthalmitis at the Pusan National University Hospital between January 2006 and December 2020. All patients were classified into six groups based on the etiology of endophthalmitis:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
1
3
0
4
Order By: Relevance
“…The occurrence of endophthalmitis depends on the patient's immune status and the virulence/dose of the organisms. As far as the organisms responsible for endophthalmitis are concerned, one study found that Staphylococcus was the most commonly isolated organism [10]. In another study, it was found that Streptococcus viridans frequently cause aggressive but sometimes delayed endophthalmitis after IVT injections [11].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of endophthalmitis depends on the patient's immune status and the virulence/dose of the organisms. As far as the organisms responsible for endophthalmitis are concerned, one study found that Staphylococcus was the most commonly isolated organism [10]. In another study, it was found that Streptococcus viridans frequently cause aggressive but sometimes delayed endophthalmitis after IVT injections [11].…”
Section: Discussionmentioning
confidence: 99%
“…Bu farklı sonuçlara kapakların ve konjonktivanın sterilizasyonu, korneadaki kesilerinin yeri, boyutu, stabilitesi, hastanın immun durumu ve cerrahide kullanılan tampon maddelerin özellikleri gibi diğer faktörlerin etkili olduğu düşünülmektedir. 22,24 İntravitreal Tamponlar:…”
Section: Pars Plana Vitrektomilerden Sonra Gelişen Endoftalmilerdeki ...unclassified
“…Sıvı tamponatlar, hava, gaz ve silikon yağına göre daha az yüzey gerilimine sahip oldukları için postoperatif erken dönemde sızıntı ve hipotoni riski yüksektir. 3,6,16,[22][23][24][25] Shimada ve ark. 23 gaz yada hava tamponat uyguladığı olguların %9'unda postoperatif hipotoni gözlerken, serum fizyolojik uyguladıkları olgularında hipotoni görülme oranın %20 düzeyine çıktığını bildirmiştir.…”
Section: Pars Plana Vitrektomilerden Sonra Gelişen Endoftalmilerdeki ...unclassified
See 2 more Smart Citations